Beyond expulsion : Jews, Christians, and Reformation Strasbourg - Kaplan, Debra (Stanford studies in Jewish history and culture., 2011)
Beyond Expulsion is a history of Jewish-Christian interactions in early modern Strasbourg, a city from which the Jews had been expelled and banned from residence in the late fourteenth century. This study shows that the Jews who remained in the Alsatian countryside continued to maintain relationships with the city and its residents in the ensuing period. During most of the sixteenth century, Jews entered Strasbourg on a daily basis, where they participated in the city's markets, litigated in its courts, and shared their knowledge of Hebrew and Judaica with Protestant Reformers. By the end of.